Use of Artificial Intelligence for Children's Story Writers - Sari, Dina Purnama (Journal of Language Development and Linguistics, 2024)
Artificial intelligence is one of the media that can be used by children's story writers. With this media, writers can express creative ideas and vary their reading media. The method used is descriptive qualitative with secondary data based on phenomena in society. The result is that by using artificial intelligence, variations in children's reading are obtained. The implication is that it is hoped that there will be more varied development of children's stories.